(3TQM GdYRj aj GdJUQjas - (3GdJaJGRGfj, SYO GdOjf, eSYhO Hf YeQ Hf YHO Gddg, J(B793(3g`s
(3ChdgG (B:s
(3aj gPG GdeNJUQ eG bQCJg aj Yde GdJUQja hef Gddg GdGSJYGfI hEdjghEdjg GdRdai hgh MSH ef Jhcd Ydjg (B((3hcai(B) (3ajgG CfG CTQY aj GdebUhO HYhf Gddg Gdedc GdeYHhOs
(3BNQgG (B:s
(3hcPG OMQLI hGMOI hOMQLI dWjaI hfMhgG hGfWdGbI hGMOI ddeQI hMSfI hbHjMI Ch ZjQgG ddfhY hcPG GdHhGbjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 219s
(3eYLe GdeDdajf(B: 3 / 849s
(3cTa GdXfhf(B: 2 / 1139s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdUQas